(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
Employers increasingly began to pay attention to the ratio of the level of well-being of employees and the effectiveness of their work. The pattern is quite simple: if there are health problems, difficulties in school or in the family, an employee cannot devote enough time and resources to work processes. In order to increase employee engagement, companies introduce well-being programs, since the main need of the staff is personal well-being.